Impact of FAAH genetic variation on fronto-amygdala function during emotional processing - Gärtner, Anne; Witt, Stephanie (European archives of psychiatry and clinical neuroscience, 2019)
Recent translational studies identified a common endocannabinoid polymorphism, FAAH C385A, in the gene for the fatty acid amide hydrolase (FAAH). This polymorphism alters endocannabinoid anandamide levels, which are known to be involved in the fronto-amygdala circuitry implicated in mood regulation and anxiety-like behaviors. While it has been shown that the variant that selectively enhances fronto-amygdala connectivity at rest is associated with decreased anxiety-like behaviors, no study so far has investigated whether this finding of FAAH-related differential plasticity extends to task-related differential functional expression and regulation during negative emotional processing. Using an imaging genetics approach, this study aimed to replicate and extend prior findings by examining functional activity and task-related connectivity in fronto-amygdala regions during emotion reactivity and emotional down-regulation of negative affect. Therefore, 48 healthy young adults underwent a functional MRI resting state measurement, completed an emotion regulation paradigm and provided self-reports on anxiety and use of emotion regulation strategies. In line with previous studies, preliminary evidence suggests that A-allele carriers demonstrate stronger fronto-amygdala connectivity during rest. In addition, exploratory whole-brain analyses indicate differential functional activity of A-allele carriers during emotion reactivity and emotion regulation. There were no associations with anxiety-related self-reports and use of emotional regulation strategies. Further research using larger samples and polygenic approaches is indicated to clarify the precise role and its underlying mechanisms in emotion processing.